Critical Minerals for Energy Transition and Sustainable Development in Africa - (:unkn) unknown (My University, 2024)
The ongoing energy transition from fossil fuels to renewable energies could have contrasting effects on African economies, particularly through increased extraction of metals critical to this transition. This paper describes the opportunities and challenges posed by the development of extraction of these metals. While Africa's share of global reserves and production is on the rise, it remains far from its potential. Factors such as lack of investment in transport and governance issues are likely to increase exploration and mining costs on the continent, and hold back the development of the sector.
Keywords: African Research